Quantum wave packet study of S(1D)+HD reaction - Gogtas, F; Bulut, N; Akpinar, S (Elsevier Science Bv, 2005)
The time-dependent real wave packet method has been used to study S(D-1) + HD reaction. State-to-state and state-to-all reactive scattering probabilities for a broad range of energy are calculated at zero total angular momentum. The probabilities for J> 0 are estimated from accurately computed J=0 probabilities by using J-shifting approximation. The integral cross-sections are calculated for a large energy range. © 2005 Elsevier B.V. All rights reserved.
Keywords: reaction dynamics; wavepacket study; S plus HD